EFFECT OF MATERIAL AND FERMENTATION TIME ON QUALITY AND DIGESTIBILITY OF COMPLETE FEED, AVERAGE DAILY GAIN OF BLIGON GOAT AND FARMER’S INCOME - Suwignyo, B.; Munawaroh, L.L.; Budisatria, I .G S. (Journal of the Indonesian Tropical Animal Agriculture, 2015)
The objectives of this research were to determine efect of material and fermentation time on qualityand digestibility of fermented complete feed, average daily gain (ADG) of Bligon goats and farmer’sincome. The research was conducted during twelve weeks in the housing of goat farmers atPurwomanunggal farmers’ group, Panggang, Gunung Kidul district. Fifteen Bligon male goats, 8 monthsof age and 12 to 15 kg of body weight, were randomly divided into three treatments, each groupsconsisted of five goats. The treatments were: control feed (R0 ), one week fermented complete feed (R1),and two weeks fermented complete feed (R2). Data were analyzed with ANOVA based on one waycompletely randomized design and continued with Duncan's multiple range tests for significantdifferences. Result showed that complete feed fermented for two weeks had darker color and strongerodors compared with one week fermentation. Both fermented complete feed (one and two weeks) hadsoft textures, no fungi with pH ranged from 4.5 to 5.0. Total digestible nutrient (TDN) intake wassignificantly affected by the treatment. The treatment had no significant effect on acid detergent fiber(ADF) and neutral detergent fiber(NDF) digestibility, average daily gain, and farmer’s income.